The Impact of "Spiritual Tour" Based Panel Discussion Learning on Spiritual Intelligence and Emotional Intelligence - I Wayan Suwendra; I Wayan Widiana (Jurnal Pedagogi dan Pembelajaran, 2023)
Many students have high intellectual intelligence, but only a few have good spiritual and emotional intelligence. This is because the learning process that is carried out only focuses on applying conventional learning models. This study aims to determine the effect of panel discussions based on "spiritual tours" on spiritual and emotional intelligence. This research belongs to the type of quasi-experimental research design in the form of a posttest-only control design. The population in the study amounted to 105 students. Samples were taken by random sampling technique, amounting to 66 students. The data collection method used is standardized tests, both spiritual and emotional intelligence tests. The analysis technique uses MANOVA with the help of SPSS. The results showed that the analysis of the Pilae Trace, Wilks' Lambda Hotelling's Trace, and Roy's Largest Root showed that the F coefficient was 9535.67b with a value of Sig. 0.00. Analysis of Tests of Between-Subjects Effects shows an F value of 5.79 with Sig. 0.02, smaller than 0.05, indicates an effect of learning with a spiritual tour-based panel discussion learning model on spiritual intelligence. Moreover, the Tests of Between-Subjects Effects analysis results show an F value of 2.53 with Sig. 0.02, which is smaller than 0.05. It shows a big influence between learning with the spiritual tour-based panel discussion learning model on emotional intelligence. Based on these results, the panel discussion learning model based on spiritual tours simultaneously or partially impacts spiritual and emotional intelligence.